Role of platelet gene polymorphisms in ischemic pediatric stroke subtypes: a case-control study - Čeri, Andrea (Croat Med J, 2020)
AIM: To assess the role of human platelet antigens (HPA), P-selectin gene (SELP) polymorphisms, and HPA and SELP haplotypes with factor V (FV) R506Q in ischemic pediatric stroke (IPS) subtypes: cerebral sinovenous thrombosis (CSVT), perinatal (PAIS), and childhood (CAIS) arterial ischemic stroke. METHODS: This case-control study enrolled 150 children with confirmed IPS and 150 age- and sex-matched controls. FV R506Q and HPA-1 were genotyped with CVD StripAssay®, HPA-2 and HPA-3 with real-time polymerase chain reaction, SELP S290N, V599L, and T715P with high resolution melting analysis, and SELP N562D with sequence-specific polymerase chain reaction. RESULTS: HPA-1b allele (odds ratio [OR] 2.75, 95% confidence interval [CI] 1.02-7.42, P = 0.048) and HPA-1a2a3b (OR 5.46, 95% CI 1.51-19.76, P = 0.011), HPA-1b2a3a (OR 7.00, 95% CI 1.25-39.13, P = 0.028), and HPA-1b2b3a (OR 11.39, 95% CI 1.39-92.95, P = 0.024) haplotypes increased the risk for CSVT. HPA-3b allele was significantly associated with 2-fold lower risk for PAIS (OR 0.49, 95% CI 0.26-0.89, P = 0.020) and CAIS (OR 0.47, 95% CI 0.26-0.86, P = 0.014) and non-significantly associated with increased risk for CSVT (OR 6.43, 95% CI 0.83-50.00, P = 0.022). HPA-1a2b3a haplotype was significantly associated with CAIS (OR 6.76, 95% CI 2.13-21.44, P = 0.001). The inclusion of FV R506Q in SELP haplotype analysis increased the risk for PAIS 4-fold in QNDVT carriers (OR 8.14, 95% CI 0.93-71.33, P = 0.060) compared with NDVT haplotype (OR 2.45, 95% CI 0.98-6.18, P = 0.058), but the result was not significant. CONCLUSION: Individual HPAs, and particularly HPA haplotypes, are involved in IPS subtypes pathogenesis. A possible risk-inducing synergistic effect of SELP haplotypes with FV R506Q is restricted to PAIS only.